Long-Term Clinical Benefit in EGFR-Mutant Lung Adenocarcinoma With Local Squamous Cell Carcinoma Transformation After EGFR TKI Resistance: A Case Report - Ye, Junru; Ma, Yutong; Ou, Qiuxiang; Yan, Junrong; Ye, Bin; Li, Yuping (Frontiers in Oncology, 2022)
The histological transformation from adenocarcinoma (ADC) to squamous cell carcinoma (SCC) is rare but recurrently occurs post TKI treatment in EGFR-mutated non-small cell lung cancer patients with a very limited number of clinical cases published. The outcome of patients after SCC onset is poor as no established treatment guidelines were available. Here we report a case who was initially diagnosed with lung ADC with EGFR L858R driver mutation and demonstrated a partial response (PR) to gefitinib for 27 months before disease progression. The rapidly progressive lung metastatic lesions were determined as an SCC histology with positive PD-L1 expression. Besides EGFR L858R, the metastatic SCC harbored the amplification of CD274 and PDCD1LG2 detected by targeted next-generation sequencing (NGS), which encode PD-L1 and PD-L2, respectively. The disease remained stable on the combination therapy of pembrolizumab plus chemotherapy for eight months until the primary ADC lesion progressed. After the failure of progressed primary ADC lesion with radiotherapy and immunotherapy, systemic ADC metastases were developed in multiple locations including kidney, liver, and chest wall with EGFR L858R mutation but negative PD-L1 expression. The patient then received the combination therapy of bevacizumab plus chemotherapy and the disease remained stable for five months. Since August 2021, afatinib has been administrated which led to a PR and the disease has remained stable up till present. This study demonstrated a primary lung ADC who developed systemic ADC metastases and local SCC transformation with distinct molecular features. The patient has achieved long-term clinical benefit upon multiple lines of chemotherapy and immunotherapy, which provided valuable insight into the treatment of advanced SCC-transformed lung ADC patients.